2016
DOI: 10.1063/1.4960487
|View full text |Cite
|
Sign up to set email alerts
|

A two-compartment microfluidic device for long-term live cell detection based on surface plasmon resonance

Abstract: A two-compartment microfluidic device integrated with a surface plasmon resonance (SPR) interferometric imaging system has been developed for long-term and real-time cell detection. The device uses a porous membrane sandwiched between two chambers to obtain an exact medium exchange rate and minimal fluid shear stress for cell culture. The two-compartment device was optimized by COMSOL simulations and fabricated using Poly (dimethylsiloxane) elastomer replica molding methods. To confirm the capability of the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…The latter has a higher spatial resolutions and the former has a better sensitivity. By monitoring the time-lapsed SPR images of single living cells during various types of physiological and biological stimulations, important spatial and dynamic information regarding the cell-substrate interactions (Giebel et al, 1999), cell migrations (Smith et al, 2004), osmotic responses (Wang et al, 2012a), ligand-receptor binding kinetics (Wang et al, 2012b, 2014), signaling pathways (Deng et al, 2016), protein activation dynamics (Peng et al, 2018), and living cancer cell drug responses (Wang et al, 2018) have been obtained. For instances, existing studies have clearly demonstrated that SPRi techniques were capable for mapping the mass density as well as the membrane integrity at single cell level (Yanase et al, 2010; Wang et al, 2012b; Yang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The latter has a higher spatial resolutions and the former has a better sensitivity. By monitoring the time-lapsed SPR images of single living cells during various types of physiological and biological stimulations, important spatial and dynamic information regarding the cell-substrate interactions (Giebel et al, 1999), cell migrations (Smith et al, 2004), osmotic responses (Wang et al, 2012a), ligand-receptor binding kinetics (Wang et al, 2012b, 2014), signaling pathways (Deng et al, 2016), protein activation dynamics (Peng et al, 2018), and living cancer cell drug responses (Wang et al, 2018) have been obtained. For instances, existing studies have clearly demonstrated that SPRi techniques were capable for mapping the mass density as well as the membrane integrity at single cell level (Yanase et al, 2010; Wang et al, 2012b; Yang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%